Why Conventional Engineering Laws Are Irrational, and a Paradigm Shift that Results in Rational Laws (Global Journals of Research in Engineering, 2022)
Conventional engineering laws are irrational for three reasons When the laws are applied to nonlinear behavior they have three variables to describe how two variables are related they are founded on Fourier s erroneous claims that dimensions can rationally be assigned to numbers and dimensions can rationally be multiplied or divided Until now it has been globally accepted that parameter symbols in rational equations represent numerical value and dimension The proposed paradigm shift requires that parameter symbols in equations represent only numerical value and if an equation is quantitative the dimension units that underlie parameter symbols must be specified in an accompanying nomenclature The proposed paradigm shift results in laws and equations that are dimensionally homogeneous because they are dimensionless The new laws are analogs of y f x The new laws state that the numerical value of parameter y is a function of the numerical value of parameter x and the function may be proportional linear or nonlinear The new laws are rational because they always have only two variables they do not require that dimensions be assigned to numbers and they do not require that parameter dimensions be multiplied or divided The new laws make it much simpler to learn and apply engineering science because they always contain only two variables and because all parameters such as h and E that were created by assigning dimensions to numbers are abandoned They are not replaced because they are not necessary
Keywords: dimensional homogeneity; dimensions; irrational equations; irrational laws; newton’s laws; paradigm shift